2015
DOI: 10.1016/j.biomaterials.2014.10.078
|View full text |Cite
|
Sign up to set email alerts
|

Lithography-free fabrication of reconfigurable substrate topography for contact guidance

Abstract: Mammalian cells detect and respond to topographical cues presented in natural and synthetic biomaterials both in vivo and in vitro. Micro- and nano-structures influence the adhesion, morphology, proliferation, migration, and differentiation of many phenotypes. Although the mechanisms that underpin cell-topography interactions remain elusive, synthetic substrates with well-defined micro- and nano-structures are important tools to elucidate the origin of these responses. Substrates with reconfigurable topography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…Ideally, engineered tissue scaffolds must provide a platform onto which cells can adhere, proliferate, and differentiate . However, the scaffolding not only influences these cellular processes but can also affect cell behaviors . As a result, exploring scaffolds are essential to understand the effects of different structures on cell growth and proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideally, engineered tissue scaffolds must provide a platform onto which cells can adhere, proliferate, and differentiate . However, the scaffolding not only influences these cellular processes but can also affect cell behaviors . As a result, exploring scaffolds are essential to understand the effects of different structures on cell growth and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, the scaffolding not only influences these cellular processes but can also affect cell behaviors. [11][12][13][14] As a result, exploring scaffolds are essential to understand the effects of different structures on cell growth and proliferation. For example, aligned fibers and anisotropic scaffolds can emulate the environment of cells and guide cell growth (such as fibroblast).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 On a cellular level, surface structures in the low micrometre range can guide adhesion and differentiation. [26][27][28][29] Parallel groove-ridge structures can cause cell contact guidance of many cell types on different materials [30][31][32][33] with the groove depth becoming more important as the grooves become deeper. 26,30,31,34 In addition, it has been shown that human mesenchymal stem cells (hMSC) guided towards elongation tend to differentiate into osteoblasts, whereas rounded ones are more prone to differentiate towards adipogenic cells.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The effect of nanoscale matrix features on cell functions has been confirmed by multitudes of in vitro studies, which utilize a variety of tools to produce cell substrates containing nano-grooves, pores, and ridges with widths ranging between 100-500 nm and depths of 100-380 nm. [9][10][11][12][13] These features affect patterning of human gingival fibroblasts, 14 porcine periodontal ligament epithelial cells and osteoblasts, 15 modulate cell morphology and function, 16 and promote attachment and spreading of epithelial cells. 17 In addition to commonly utilized silicon and poly(styrene) substrates, thermoresponsive polymers have been utilized to spatially control fibroblast adhesion and temperature-responsive detachment.…”
Section: Introductionmentioning
confidence: 99%